Ritual Language Cultural Values in the Tradition of the Toba Batak Tribe ini Toba Samosir: Anthropolinguistic Study - Situmorang, Rahel Theresia Rodame; Silaban, Immanuel; Siregar, Arjuna Junifer; Tifany; Sibarani, Robert (Raja Zulkarnain Education Foundation, 2025)
This research examines the form, function and meaning of ritual language in the Toba Batak community in Toba Samosir Regency through an anthropolinguistic approach. Ritual language is an important tool in traditional ceremonies which not only functions as a means of communication, but also as a medium for transmitting cultural values, social systems and ethnic identity. This research uses descriptive qualitative methods with participatory observation techniques, and analysis of traditional speech texts such as umpasa, mangupa prayers, and kinship greetings. The results of the research show that the Toba Batak ritual language reflects the dalihan natolu social system which emphasizes balanced social relations, respect for ancestors and clan solidarity. Traditional speeches such as umpasa contain moral values such as honesty, sincerity, hard work and mutual cooperation. Even though modernization has brought changes in the context of ritual language use, the Toba Batak community still maintains core values through adapting forms and media. Thus, the Toba Batak traditional language functions as a living and dynamic cultural structure, representing a close relationship between language, culture and ethnic identity.